Pengaruh Tenaga Kerja dan Teknologi Terhadap Pertumbuhan Industri di Jawa Timur - Putra, Arvino Risqie Perdana Putra; Sitohang, Arga Christian (Nirta Learning Centre, 2024)
The purpose of this study was to analyse the effect of labour and modern technology on income growth of the coffee shop industry in East Java. This research uses descriptive quantitative method. Sampling in this study using saturated sample technique. The samples selected for this study were 50 coffee shop businesses in East Java. The results revealed that labour has no simultaneous and significant effect on the growth of the coffee shop industry, while technology has a simultaneous and significant effect on the growth of the industry. It is hoped that this information can be an input for coffee shop businesses in determining the specifications of the workforce and technology used, and can analyse the effect of labour and modern technology on the growth of their coffee shop business.